Dietary supplementation with Cyberlindnera jadinii improved growth performance, serum biochemical Indices, antioxidant status, and intestinal health in growing raccoon dogs (Nyctereutes procyonoides) - Zhao, Dehui; Liu, Hanlu; Zhang, Haihua; Liu, Keyuan; Zhang, Xinyu; Liu, Qian; Wu, Yan; Zhang, Ting; Zhang, Qiaoru (Frontiers in Microbiology, 2022)
This study was conducted to investigate whether different dietary Cyberlindnera jadinii levels affect growth performance, serum immunity, antioxidant capacity, and intestinal microbiota in growing raccoon dogs. Forty-five healthy male raccoon dogs were randomly assigned to three treatment groups, with 15 raccoon dogs per group. Each raccoon dog was housed in an individual cage. The raccoon dogs in the three groups were fed diets supplemented with Cyberlindnera jadinii at dosages of 0 (N group), 1 × 109 (L group) and 5 × 109 CFU/g (H group). A 7-day pretest period preceded a formal test period of 30 days. The results showed that Cyberlindnera jadinii in the L and H groups improved average daily gain (ADG) (P < 0.05) and decreased the ratio of feed to weight (F/G) (P < 0.05). Serum immunoglobulins A and G levels were increased in the L and H groups compared to the N group (P < 0.05). Cyberlindnera jadinii in the L and H groups increased serum superoxide dismutase activity (P < 0.05), and serum glutathione peroxidase activity was increased in the L group compared to the N group (P < 0.05). The relative abundance of Firmicutes and Actinobacteriota were increased, and the relative abundance of Bacteroidota was decreased in the L and H groups compared to the N group (P < 0.05). The relative abundance of Proteobacteria and Cyanobacteria was increased in the H group compared to the other two groups (P < 0.05). The ratio of Firmicutes to Bacteroidetes in the Cyberlindnera jadinii supplementation groups increased compared with the N group (P < 0.05). The relative abundance of Megasphaera and Bifidobacterium were increased, and the relative abundance of Prevotella was decreased in the L and H groups compared to the N group (P < 0.05). The relative abundance of Dialister was increased, while the relative abundance of Blautia was decreased in the H group compared to the other two groups (P < 0.05). The relative abundance of Agathobacter was decreased in the H group compared to the N group (P < 0.05). In conclusion, dietary supplementation with Cyberlindnera jadinii increased growth performance, serum immunity, antioxidant capacity, and improved intestinal microbiota in growing raccoon dogs. Cyberlindnera jadinii can therefore be used as a growth promoter in raccoon dogs.